In vitro and alternative animal models to evaluate the biocompatibility of natural latex-calcium phosphate-based polymer - Miranda, Matheus Carlos Romeiro [UNESP] (2022)
The number of mammalian animals killed for research purposes has increased significantly in recent years. For this reason, several alternative animal models have been widely used. In this study, two phases of calcium phosphates synthesized by the sol-gel method were added by precipitation to the surface of the natural rubber latex membranes for bone applications. The toxicity eluates from the membrane were evaluated by in vitro assays through cell viability and hemolysis; and by in vivo models using Caenorhabditis elegans worms and zebrafish embryos through survival analysis. Hemolysis levels were less than 3%, which indicates that there was no significant hemolytic activity. It was demonstrated that latex presents enzymes that can dissociate osteoblasts MC3T3, so it was necessary to eliminate these enzymes to obtain a good adhesion and cellular proliferation without morphological alterations. The eluates of membranes did not reduce the survival of Caenorhabditis elegans larvae for 48 h of analysis, except for a hydroxyapatite sample incubated for 5 days. In the zebrafish embryotoxicity assay for 96 hpf of analysis, 60% of embryos survived and there was no evidence of embryos with malformation or developmental delay. In summary, alternative animal models, which are not commonly used to assess biocompatibility, have provided reliable in vivo results that allow suggesting the use of these membranes in the bone biomedical.